Metal-cutting machine tools / [by] A. Gavryushin, N. Lisitsyn [and] O. Trifonov. Edited by N. Acherkan. Translated from the Russian by Nicholas Weinstein. - Gavri͡ushin, A. A.
Translation of v. 1, pt. 1 (romanized: Metallorezhushcie stanki), edited by N. S. Acherkan.